Significant association of increased PD-L1 and PD-1 expression with nodal metastasis and a poor prognosis in oral squamous cell carcinoma. Issue 7 (July 2018) - Maruse, Y.; Kawano, S.; Jinno, T.; Matsubara, R.; Goto, Y.; Kaneko, N.; Sakamoto, T.; Hashiguchi, Y.; Moriyama, M.; Toyoshima, T.; Kitamura, R.; Tanaka, H.; et al.
Abstract: Programmed cell death ligand 1 (PD-L1) and its receptor PD-1 are immune checkpoint molecules that attenuate the immune response. Blockade of PD-L1 enhances the immune response in a variety of tumours and thus serves as an effective anti-cancer treatment. However, the biological and prognostic roles of PD-L1/PD-1 signalling in oral squamous cell carcinoma (OSCC) remain to be elucidated. The purpose of this study was to examine the correlation of PD-L1/PD-1 signalling with the prognosis of OSCC patients to assess its potential therapeutic relevance. The expression of PD-L1 and of PD-1 was determined immunohistochemically in 97 patients with OSCC and the association of this expression with clinicopathological characteristics was examined. Increased expression of PD-L1 was found in 64.9% of OSCC cases and increased expression of PD-1 was found in 61.9%. Univariate and multivariate analysis revealed that increased expression of PD-L1 and PD-1 positively correlated with cervical lymph node metastasis. The expression of CD25, an activated T-cell marker, was negatively correlated with the labelling index of PD-L1 and PD-1. Moreover, the patient group with PD-L1-positive and PD-1-positive expression showed a more unfavourable prognosis than the group with PD-L1-negative and PD-1-negative expression. These data suggest that increased PD-L1 and PD-1 expression is predictive of nodal metastasis and a poor prognosis and is possibly involved in cancer progression via attenuating the immune response.